MUNICIPAL WASTEWATER TREATMENT WITH BENTONITE FROM MILOS ISLAND, GREECE - Bourliva, A.; Michailidis, K.; Sikalidis, C.; Filippidis, A.; Apostolidis, N. (Bulletin of the Geological Society of Greece, 2010)
Bentonite clay minerals belonging to the smectite group have a wide range of chemical and industrial uses. The structure and chemical composition, exchangeable ion type and small crystal size of smectite are responsible for several properties, including a large chemically active surface area and a high cation exchange capacity. A wastewater treatment using bentonite from Milos island, Greece, was investigated. Raw wastewater sample (influent) from the wastewater treatment plant (WTP) of the city of Kilkis, Northern Greece was treated using bentonite in conjunction with chemical coagulants (polyaluminium chloride-PAC and cationic polyelectrolyte), in batch type experiments. The removal of suspended solids (SS), chemical oxygen demand (COD), nitrate ion, ammonium ion, phosphate ion, and toxic metals were evaluated. The treatment gave overflowed clear water improved concerning the quality parameters. The bentonite adding prior to flocculation resulted in effective removal of heavy metals such as chromium and copper. Additionally, the bentonite removed nitrogen compounds with relatively high efficiency, while the clay presence highly improved the COD removal. The quality parameters after treatment were improved fulfilling the requirements for disposition as downstream, irrigation, swimming and fish waters.